Clinical Application of Flexible Endoscopic Evaluation of Swallowing in Stroke - Pisegna, Jessica M.; Murray, Joseph (Seminars in Speech and Language, 2018)
This article aims to review the use of laryngoscopy to assess swallowing function in the stroke population. Since its inception in 1988, fiberoptic endoscopic evaluation of swallowing (FEES) has become an established procedure with distinct objective findings and practical applications, enabling many to choose it as the primary instrumental tool in evaluating poststroke dysphagia. In this article, we outline the decision-making process of when to use FEES. We highlight considerations for the acute stroke patient and visual signs that guide decision making during a FEES, such as secretions, swallowing frequency, and pharyngeal squeeze elicitation. The application of the ice chip protocol for stroke patients who have been nil per os is discussed, along with common observable events on FEES performed on stroke patients like a delay, penetration/aspiration, and bolus retention. Finally, we briefly review testing interventions and follow-up readiness with FEES.
Keywords: FEES; stroke; dysphagia